Case report: Clinical and genetic characteristics of heterozygous CaSR variants in three Chinese females with familial hypocalciuric hypercalcemia type 1: a report of three cases - Zhang, Ruxuan; Hu, Tingting; Wang, Shuai; Cheng, Yiping; Luo, Dandan; Zheng, Dongmei; Zhou, Xinli (Frontiers in Genetics, 2025)
BackgroundFamilial hypocalciuric hypercalcemia (FHH) is an autosomal dominant disorder and represents a rare cause of hypercalcemia. It stems from variants in the calcium-sensing receptor gene (CaSR), G-protein subunit alpha11 gene (GNA11), or adaptor-related protein complex 2 gene (AP2S1), among which variants in the CaSR gene are the most prevalent. However, challenges in the current diagnosis of FHH persist, owing to the overlap in clinical features with primary hyperparathyroidism (PHPT).Case presentationThe three reported patients demonstrated similar clinical presentations such as hypercalcemia and relative hypocalciuria. In two of them, the parathyroid hormone (PTH) level was elevated, while in one, it was normal. Initially, all of them received conventional hypocalcemic treatment. After comprehensive medical history collection and auxiliary examination were conducted to exclude other causes of hypercalcemia, whole exome sequencing (WES) and sanger sequencing were carried out. The results showed that the three patients carried different variants sites in the CaSR gene, namely, c.887G>A, c.2027 > G, c.1608 + 3A>T and c.332C>T. In addition, c.887G>A was also found in the son and grandson of patient 1. The analysis of the conservation of homologous species and the prediction of protein structure for all variant sites demonstrated that due to the heterozygous variants in CaSR, relatively conserved amino acids were altered, affecting the interaction forces between adjacent amino acids, resulting in changes in the protein structure, which might affect the function of the protein.ConclusionIn conclusion, we report three cases of FHH1 with different heterozygous variant sites in the CaSR gene. This study has expanded the spectrum of variants. It is of great significance for the genetic screening, diagnosis, counseling, and research of hypercalcemia-related genes and become a key resource for enhancing clinicians’ understanding of FHH1.